Osteoporosis and antithrombotic therapy - N. V. Brailova; E. N. Dudinskaya; V. A. Kuznesova; O. N. Tkacheva (Российский кардиологический журнал, 2021)
Anticoagulant and antiplatelet agents are used to prevent stroke and thromboembolic events. There is insufficient data on the effect of these drugs on bone tissue. In addition, the available data are ambiguous, which increases suspicion when used in individuals at high risk of osteoporosis. The article provides data on the effect of anticoagulant and antiplatelet agents on bone metabolism, bone mineral density and the fracture risk. Literature data indicate a negative effect of heparin on bone tissue, which is increase the risk of fractures. Low molecular weight heparins has lower effect on bone tissue than heparin. It is known that vitamin K antagonists significantly affect bone metabolism and markers of bone formation, however, data on the effect on bone mineral density and the risk of fractures are contradictory. Direct oral anticoagulants are relatively safe in relation to bone tissue. Data on the effects of antiplatelet drugs on bone are ambiguous.